Nucleic acid polymers: Broad spectrum antiviral activity, antiviral mechanisms and optimization for the treatment of hepatitis B and hepatitis D infection - Vaillant, Andrew (Antiviral research, 2016)
Antiviral polymers are a well-studied class of broad spectrum viral attachment/entry inhibitors whose activity increases with polymer length and with increased amphipathic (hydrophobic) character. The newest members of this class of compounds are nucleic acid polymers whose activity is derived from the sequence independent properties of phosphorothioated oligonucleotides as amphipathic polymers. Although the antiviral mechanisms and broad spectrum antiviral activity of nucleic acid polymers mirror the functionality of other members of this class, they exert in addition a unique post entry activity in hepatitis B infection which inhibits the release of HBsAg from infected hepatocytes. This review provides a general overview of the antiviral polymer class with a focus on nucleic acid polymers and their development as therapeutic agents for the treatment of hepatitis B/hepatitis D. This article forms part of a symposium in Antiviral Research on ‘‘An unfinished story: from the discovery of the Australia antigen to the development of new curative therapies for hepatitis B.’’ •NAPs block viral entry in many viruses including hepatitis B and hepatitis D.•NAPs also have a post-entry activity against HBV consistent with HBsAg release inhibition.•The post-entry activity of NAPs appears essential for antiviral activity in vivo.•NAPs have therapeutic effect against chronic HBV and HDV infection in humans.•Elimination of HBsAg by NAPs may improve the effect of immunotherapy.